Discovery of a second species of Aesalini from continental China, with description of the new species and its third instar larva (Coleoptera: Scarabaeoidea: Lucanidae) - Huang, Hao; Bi, Wen-Xuan; Li, Li-Zhen (Zootaxa, 2009)
Aesalus zhejiangensis Huang & Bi, sp. nov. is described from Mt. Fengyangshan, southern Zhejiang, China. It is the second species of the lucanid genus Aesalus Fabricius known from continental China. This new species is similar to the Indo-Chinese species Aesalus satoi, but can be distinguished by the longer canthus, male with shorter non-sclerotized distal portion of penis (medial lobe of parameres), and female genitalia with longer styli. A checklist of Aesalini and a key to the Old World species are given. Female genitalia and larval morphology are described in detail for the new species and discussed for the higher classification of Aesalini. The current state of Aesalini systematics and phylogeny is discussed.